Investigating the impacts of regulatory focus and political skill within a social media context. (February 2019) - Zivnuska, Suzanne; Carlson, Dawn S.; Carlson, John R.; Harris, Ranida B.; Harris, Kenneth J.
Abstract: Based on Regulatory Focus theory (Higgins, 1997), we extend existing findings to empirically investigate how regulatory focus and political skill are related within a social media context. Though social media is commonly used in the workplace, it has not yet been studied in relation to the competing paths of regulatory focus (prevention and promotion) and political skill. Our sample included 312 full-time employees. We found a negative path from prevention-focus through political skill dis-incentivizes social media use for enhancement of work mood and work network. A positive path from promotion-focus through political skill incentivizes employees to engage in social media use for enhancement of work mood and work network. Implications and opportunities for future research are discussed. Highlights: Two self-regulatory paths inform employee choices to use social media at work. Prevention-focus is related to less use of political skill and social media. Promotion-focus is related to more use of political skill and social media. Social media can be used to enhance work mood and work network.